Effect of moderate to high intensity aerobic exercise on blood pressure in young adults: The TEPHRA open, two-arm, parallel superiority randomized clinical trial. (June 2022) - Williamson, Wilby; Lewandowski, Adam James; Huckstep, Odaro John; Lapidaire, Winok; Ooms, Alexander; Tan, Cheryl; Mohamed, Afifah; Alsharqi, Maryam; Bertagnolli, Mariane; Woodward, William; Dockerill, Cameron; McCourt, Annabelle; et al.
Summary: Background: Exercise is advised for young adults with elevated blood pressure, but no trials have investigated efficacy at this age. We aimed to determine whether aerobic exercise, self-monitoring and motivational coaching lowers blood pressure in this group. Methods: The study was a single-centre, open, two-arm, parallel superiority randomized clinical trial with open community-based recruitment of physically-inactive 18–35 year old adults with awake 24 h blood pressure 115/75mmHg-159/99 mmHg and BMI<35 kg/m 2 . The study took place in the Cardiovascular Clinical Research Facility, John Radcliffe Hospital, Oxford, UK. Participants were randomized (1:1) with minimisation factors sex, age (<24, 24–29, 30–35 years) and gestational age at birth (<32, 32–37, >37 weeks) to the intervention group, who received 16-weeks aerobic exercise training (three aerobic training sessions per week of 60 min per session at 60–80% peak heart rate, physical activity self-monitoring with encouragement to do 10, 000 steps per day and motivational coaching to maintain physical activity upon completion of the intervention. The control group were sign-posted to educational materials on hypertension and recommended lifestyle behaviours. Investigators performing statistical analyses were blinded to group allocation. The primary outcome was 24 h awake ambulatory blood pressure (systolic and diastolic) change from baseline to 16-weeks on an intention-to-treat basis. Clinicaltrials.gov registered on March 30, 2016 (NCT02723552). Findings: Enrolment occurred between 30/06/2016-26/10/2018. Amongst the 203 randomized young adults ( n = 102 in the intervention group; n = 101 in the control group), 178 (88%; n = 76 intervention group, n = 84 control group) completed 16-week follow-up and 160 (79%; n = 68 intervention group, n = 69 control group) completed 52-weeks follow-up. There were no group differences in awake systolic (0·0 mmHg [95%CI, -2·9 to 2·8]; P = 0·98) or awake diastolic ambulatory blood pressure (0·6 mmHg [95%CI, -1·4. to 2·6]; P = 0·58). Aerobic training increased peak oxygen uptake (2·8 ml/kg/min [95%CI, 1·6 to 4·0]) and peak wattage (14·2watts [95%CI, 7·6 to 20·9]) at 16-weeks. There were no intervention effects at 52-weeks follow-up. Intepretation: These results do not support the exclusive use of moderate to high intensity aerobic exercise training for blood pressure control in young adults. Funding: Wellcome Trust, British Heart Foundation, National Institute for Health Research, Oxford Biomedical Research Centre.